PENGARUH MODEL SELF DIRECTED LEARNING ‎TERHADAP ‎KEAKTIFAN DAN HASIL BELAJAR SISWA ‎PADA MATA PELAJARAN ‎PAI - Utami Santoso, Siti Rasmi; Ali Saifil Akbar; Junaidi (Wasīlah: Journal Of Sharia Sciences, 2026)
This study was motivated by the low level of student participation and learning outcomes in Islamic Religious Education (PAI), which are often caused by the dominance of passive lecture-based teaching methods. This quantitative study aimed to examine the effect of the Self-Directed Learning (SDL) model on the learning activeness and learning outcomes of eighth-grade students at SMP Al-Hikam Burneh Bangkalan. The research employed a quasi-experimental method with a posttest-only control group design. Through purposive sampling, 75 students were selected as the sample and divided into an experimental group (n = 37), which applied the SDL model, and a control group (n = 38), which used the lecture method. The data were analyzed using statistical tests that showed significant results at the level of p = 0.000 (p ≤ 0.05). The findings revealed that the average activeness score of the experimental class (39.54) was higher than that of the control class (33.21). Likewise, the average learning outcome score of the experimental class (74.70) also exceeded that of the control class (64.36). This study concludes that the SDL model effectively improves students’ active engagement and cognitive achievement in PAI learning. Educators are therefore encouraged to adopt the SDL model as an alternative learning approach to foster learner autonomy in the contemporary era.